Correlates of perceptions of police legitimacy: Do perceptions of neighborhood crime matter? - Garduno, L. Sergio (International journal of police science & management, 2021)
Police legitimacy promotes trust and cooperation between members of the public and the police. Because the police require cooperation from the public to prevent and solve crimes, having high levels of legitimacy is an important asset for them. Researchers have explored policing strategies as well as individual and neighborhood characteristics that explain levels of police legitimacy. However, no study has explored whether perceived neighborhood crimes affect perceptions of police legitimacy. This study addresses this gap in the literature by analyzing the effect that perceiving four types of neighborhood crime as a problem had on levels of police legitimacy among 1773 respondents from a city in the Appalachians. Results obtained from a series of Ordinary Least Squares models indicate that perceptions of neighborhood crime have no significant effect on police legitimacy once police performance is accounted for. Research and policy implications are discussed.